The Einstein@Home search for radio pulsars and PSR J2007+2722 discovery - Allen, B.; Knispel, B.; Cordes, J.; Deneva, J.; Hessels, J.; Anderson, D.; Aulbert, C.; Bock, O.; Brazier, A.; Chatterjee, S.; Demorest, P.; Eggenstein, H.; et al. (Institute of Physics Publishing, Inc., 2013)
Einstein@Home aggregates the computer power of hundreds of thousands of volunteers from 193 countries, to search for new neutron stars using data from electromagnetic and gravitational-wave detectors. This paper presents a detailed description of the search for newradio pulsars using PulsarALFAsurvey data from the Arecibo Observatory. The enormous computing power allows this search to cover a new region of parameter space; it can detect pulsars in binary systems with orbital periods as short as 11 minutes. We also describe the first Einstein@Home discovery, the 40.8 Hz isolated pulsar PSR J2007+2722, and provide a full timing model. PSR J2007+2722’s pulse profile is remarkably wide with emission over almost the entire spin period. This neutron star is most likely a disrupted recycled pulsar, about as old as its characteristic spin-down age of 404 Myr. However, there is a small chance that it was born recently, with a low magnetic field. If so, upper limits on the X-ray flux suggest but cannot prove that PSR J2007+2722 is at least ~100 kyr old. In the future, we expect that the massive computing power provided by volunteers should enable many additional radio pulsar discoveries.